Electron beam absorption in 3D-printed polymer samples with different infill densities. (October 2019) - Bulavskaya, A (Krasnykh); Danilova, I; Dontsov, Y; Cherepennikov, Y; Miloichikova, I; Stuchebrov, S
Abstract: In this work, we study the efficiency of electron absorption by the plastic samples produced using 3D printing with different infill densities. We investigate the influence of the print layer orientation relative to the electron beam axis on the radiation dose distribution. It is possible to produce plastic samples with different infill by fused deposition modelling. Ten polymer test samples with the infill density ranging from 10% to 100% are printed and studied experimentally using a 6 MeV electron beam of an MIB-6E betatron. GafChromic EBT3 films are used for the dose measurement. When the infill is above 70%, the difference of dose distribution uniformity cannot be distinguished for the two print layer orientations. Therefore, these samples can be used for electron beam formation.